Retrospective biomonitoring of chemical contamination in the marine coastal environment of Terra Nova Bay (Ross Sea, Antarctica) by environmental specimen banking. (December 2016) - Grotti, Marco; Pizzini, Sarah; Abelmoschi, Maria Luisa; Cozzi, Giulio; Piazza, Rossano; Soggia, Francesco
Abstract: Antarctica offers a good opportunity to investigate planetary-scale pollution and climate change, and provides baseline values for contaminants such as Trace Elements (TEs) and Persistent Organic Pollutants (POPs). Literature data on contaminant levels in the Antarctic environment indicate that long-range atmospheric transport is the primary pathway by which pollutants from surrounding continents are carried to this pristine environment. However, local contamination sources represented by the scientific stations are also not negligible. Climate change and global warming are altering the global budget of anthropogenic contaminants and their monitoring in Antarctica ecosystems is very important to protect the global environment. In this work, eighty specimens of Adamussium colbecki (Smith, 1902), a benthic Antarctic scallop, collected from 1996 to 2009 and stored in the Antarctic Environmental Specimen Bank, were analyzed to quantify TEs and POPs, including polychlorinated biphenyls (PCBs), polychlorinated naphthalenes (PCNs) and polycyclic aromatic hydrocarbons (PAHs). Metals concentrations were not affected by anthropogenic contributions, highlighting a natural accumulation with the age of the organism. Similarly, no temporal trend was found for PCNs, PCBs and PAHs. However, specimens collected during the summer 1997–98 showed enhanced concentration levels of PCBs and PAHs that could refer to a local anthropogenic source of contamination. Graphical abstract: Highlights: Trace elements and organic pollutants in specimens of A. colbecki were assessed. Trace elements occurred at natural levels throughout 1996–2009. Local contamination sources were important for some persistent organic pollutants. Long-range transport was a minor source of contaminants near the scientific station. The Antarctic specimen bank properly supported this retrospective monitoring study.